Personal growth and confinement: a spatial study of Kazuo Ishiguro’s Never Let Me Go - Nie, Zhixing; Hardev, Kaur; Manimangai, Mani (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article analyzes Kazuo Ishiguro’s Never Let Me Go (2005) through the lens of spatial theories by Henri Lefebvre, Michel Foucault, and Gaston Bachelard, focusing on the protagonist Kathy’s growth within spatial and societal constraints. By tracing Kathy’s journey from childhood at Hailsham to disillusioned adulthood, the study examines how her interactions with geographical, social, and psychological spaces shape her evolving self-awareness and identity. The novel’s depiction of clones, confined within institutions like Hailsham and the cottages, serves as a metaphor for marginalized groups, highlighting their struggles for self-assertion in oppressive systems. Spatial analysis reveals how physical spaces (e.g., Hailsham, donation centres) reflect societal control, while social spaces (e.g., Kathy’s relationships with Tommy and Ruth) influence her understanding of her role. Psychological spaces, including memories and dreams, further illuminate her growth. Ultimately, this article argues that Kathy’s journey symbolizes the resilience and agency of marginalized communities. By navigating and resisting spatial constraints, she embodies the possibility of personal growth amidst oppression. Ishiguro advocates for recognizing the humanity and dignity of those rendered invisible by societal structures. This study contributes to the scholarship on spatiality in literature by offering new perspectives on the intersections of personal growth, confinement, and identity in Never Let Me Go.